2003
DOI: 10.1080/13880200308951339
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Flavonoids fromBallota glandulosissima

Abstract: The flavonoids kumatakenin (1), pachypodol (2), 5-hydroxy-7,3',4'-trimethoxyflavone (3), velutin (4), salvigenin (5), retusin (6) and corymbosin (7) have been isolated from the aerial parts of Ballota glandulosissima Hub.-Mor & Patzak. Among them, 2-4 and 7 have not been reported previously in the genus Ballota. The antibacterial and antifungal activities of 1-4 and 6 were tested against Bacillus subtilis, Staphylococcus aureus, Staphylococcus faecalis, Echerichia coli, Pseudomonas aeruginosa, Candida albicans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In our previous studies, three diterpenoids (hispanolone, ballonigrine, dehydrohispanolone) and ten flavonoids (kumatakenin, pachypodol, 5-hydroxy-7,3′,4′-trimethoxyflavone, velutin, corymbosine, 5-hydroxy-3,7,4′-trimethoxyflavone, retusin, 5-hydroxy-7,4′-dimethoxyflavone, 5-hydroxy-3,6,7,4′-tetramethoxyflavone, ladanein) were isolated, chemically characterized, and analyzed by HPLC in different species of Ballota [6,7,13,14].…”
Section: 972mentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, three diterpenoids (hispanolone, ballonigrine, dehydrohispanolone) and ten flavonoids (kumatakenin, pachypodol, 5-hydroxy-7,3′,4′-trimethoxyflavone, velutin, corymbosine, 5-hydroxy-3,7,4′-trimethoxyflavone, retusin, 5-hydroxy-7,4′-dimethoxyflavone, 5-hydroxy-3,6,7,4′-tetramethoxyflavone, ladanein) were isolated, chemically characterized, and analyzed by HPLC in different species of Ballota [6,7,13,14].…”
Section: 972mentioning
confidence: 99%
“…Ballota species have been used in Turkish folk medicine as an antiulcer, antispasmodic, diuretic, choleretic, antihaemorrhoidal, and sedative agents [2,3]. The antimicrobial activities [4] and the antioxidant activities [5] of all Ballota species growing in Turkey was recently reported as well as the antifungal activities of some flavonoids isolated from B. glandulossima [6] and B. inaequidens [7]. The water extract of B. glandulosissima has been reported to have antinociceptive [8], antiinflammatory, and hepatoprotective activities [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that Ballota acetabulosa is used for the treatment of haemorrhoids as infusion in folk medicine (12). The antimicrobial (20) and antioxidant activities (21) of all Ballota species growing in Turkey was recently reported as well as the antifungal activities of some flavonoids isolated from Ballota glandulosissima (22). The main components of the Ballota species are flavonoids, labdane diterpenoids and phenylpropanoids (26).…”
Section: Monocytogenes Is Resistant To Different Environmental Conmentioning
confidence: 99%
“…The main components of the Ballota species are flavonoids, labdane diterpenoids and phenylpropanoids (26). In our previous studies, three diterpenoids (hispanolone, ballonigrine, dehydrohispanolone) and ten flavonoids (kumatakenin, pachypodol, 5-hydroxy-7,3',4'-trimethoxyflavone, velutin, corymbosin, 5-hydroxy-3,7,4'-trimethoxyflavone, retusin, 5-hydroxy-7,4'-dimethoxyflavone, 5-hydroxy-3,6,7,4'-tetramethoxyflavone, ladanein) were isolated, chemically characterized and analysed by HPLC in different Ballota species (15,22,(25)(26)(27). This paper is a part of our on-going studies on this genus (15,(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Monocytogenes Is Resistant To Different Environmental Conmentioning
confidence: 99%